2021
DOI: 10.1093/zoolinnean/zlaa170
|View full text |Cite|
|
Sign up to set email alerts
|

FromArgetoZenarge: adult morphology and phylogenetics of argid sawflies (Hymenoptera: Argidae)

Abstract: The Argidae is the second most diverse family of the ‘Symphyta’ with more than 900 described species. Here we present the first comprehensive phylogenetic study for the family. We compare the adult skeleton anatomy of representatives of 57 described argid genera from different biogeographic regions. We score 223 characters for 117 terminal taxa, and apply maximum parsimony inference to reconstruct the phylogeny, using equal weights and implied weights analyses. The Argidae sensu stricto, i.e. all Argidae excep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(27 citation statements)
references
References 44 publications
6
21
0
Order By: Relevance
“…Other classification schemes for Argidae recognizing more subfamilies and tribes have been proposed (e.g., Smith, 1992;Taeger et al, 2010). Malagón-Aldana et al (2021a) were unable to corroborate these, although some previously suggested tribes (e.g., Trichorhachini, Atomacerini, Dielocerini and Sterictiphorini) were retrieved as monophyletic. Revising the tribal classification of Argidae s.s. will require a denser taxon sampling than was obtained in Malagón-Aldana et al (2021a).…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…Other classification schemes for Argidae recognizing more subfamilies and tribes have been proposed (e.g., Smith, 1992;Taeger et al, 2010). Malagón-Aldana et al (2021a) were unable to corroborate these, although some previously suggested tribes (e.g., Trichorhachini, Atomacerini, Dielocerini and Sterictiphorini) were retrieved as monophyletic. Revising the tribal classification of Argidae s.s. will require a denser taxon sampling than was obtained in Malagón-Aldana et al (2021a).…”
Section: Introductionmentioning
confidence: 92%
“…An additional total evidence approach using Bayesian tree inference was performed combining the data matrix of 223 adult anatomical characters (117 taxa) (Malagón-Aldana et al, 2021a) and 85 larval characters (48 taxa) (Malagón-Aldana et al, 2021b) with the molecular dataset. For the adult morphological character matrix, seven characters (41, 45, 87, 89, 161, 162 and 175) were treated as ordered in accordance with Malagón-Aldana et al (2021a), and three additional characters (5,27,39) based on the result patterns of the larval morphology dataset (Malagón-Aldana et al, 2021b). The molecular and morphological datasets were assembled using mesquite 3.6 (Maddison & Maddison, 2019).…”
Section: Total Evidence Phylogenetic Analysis: Molecules and Morphologymentioning
confidence: 99%
See 3 more Smart Citations